2009
DOI: 10.1002/art.24574
|View full text |Cite
|
Sign up to set email alerts
|

Galectin 3 induces a distinctive pattern of cytokine and chemokine production in rheumatoid synovial fibroblasts via selective signaling pathways

Abstract: Objective. High expression of galectin 3 at sites of joint destruction in rheumatoid arthritis (RA) suggests that galectin 3 plays a role in RA pathogenesis. Previous studies have demonstrated the effects of galectins on immune cells, such as lymphocytes and macrophages. This study was undertaken to investigate the hypothesis that galectin 3 induces proinflammatory effects in RA by modulating the pattern of cytokine and chemokine production in synovial fibroblasts.Methods. Matched samples of RA synovial and sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
124
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 58 publications
7
124
0
Order By: Relevance
“…47 Moreover, the JNK and ERK signaling pathways are involved in pro-inflammatory cytokine and chemokine production in activated FLS. 48,49 Numerous studies have demonstrated that the inhibition of the JNK and ERK pathways has profound effects on the synthesis of inflammatory cytokines and modulation of acute and chronic inflammation. 50 …”
Section: Discussionmentioning
confidence: 99%
“…47 Moreover, the JNK and ERK signaling pathways are involved in pro-inflammatory cytokine and chemokine production in activated FLS. 48,49 Numerous studies have demonstrated that the inhibition of the JNK and ERK pathways has profound effects on the synthesis of inflammatory cytokines and modulation of acute and chronic inflammation. 50 …”
Section: Discussionmentioning
confidence: 99%
“…34 Several studies have shown that gal3 upregulates IL-6 in pathologic conditions. 7,8,35 We have previously shown that IL-6 plays a key role in promoting VT. 15 We therefore decided to investigate the relationship between gal3 and IL-6 during VT. The strong correlation we observed between gal3 and IL-6 expression in the vein wall led us to examine whether these were mechanistically involved in venous thrombogenesis.…”
Section: Gal3 Plays a Proinflammatory Role In The Context Of Vtmentioning
confidence: 99%
“…[5][6][7][8] Both gal3bp and gal3 are found in most normal adult tissues, mainly in epithelial and myeloid/amoeboid cells, 9 but to our knowledge they have never been previously explored in platelets (PLTs), red blood cells (RBCs), microparticles, vein walls, and venous thrombus, all critical elements that participate in VT. Gal3 is found within the nucleus, cytoplasm, cell surface, and extracellular space as a monomer, or multimer, or it is fragmented as a result of enzymatic cleavage. 10 Gal3 multimerization is known to have physiologic consequences, such as enhancing the ability of gal3 to facilitate cell-to-cell interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Recently, galectin-1 was shown to induce the production of interleukin-10 and attenuate the secretion of interferon-g in activated T cells, and galectin-3 was shown to promote the production of proinflammatory cytokines, such as interleukin-6 and tumor necrosis factor-a, in synovial fibroblasts. 16,17 A single injection of syngenic DBA/1 fibroblasts engineered to secret galectin-1 at the onset of disease abrogated experimental arthritis in mice. 18 Furthermore, microarray analysis of peripheral mononuclear cells has identified galectin-3 as a blood biomarker in the rat CIA model.…”
Section: Introductionmentioning
confidence: 99%